2005
DOI: 10.1037/0278-7393.31.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Talker Variability and Recognition Memory: Instance-Specific and Voice-Specific Effects.

Abstract: The author investigated voice context effects in recognition memory for words spoken by multiple talkers by comparing performance when studied words were repeated with same, different, or new voices at test. Hits and false alarms increased when words were tested with studied voices compared with unstudied voices. Discrimination increased only when the exact same voice was used. A trend toward conservatism in response bias was observed when test words switched to increasingly unfamiliar voices. Taken together, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 47 publications
6
58
3
Order By: Relevance
“…The present findings are, however, consistent with those in the wider literature on context effects in recognition memory (e.g., Goh, 2005;Goldinger, 1996;Lim & Goh, 2012, 2013Peretz et al, 1998). In these studies, switching the speaker of the words and the timbre of the melodies from study to test, but keeping the identity the same, resulted in poorer recognition, as compared with the conditions in which both the central (word and melody identity) and peripheral (speaker and timbre) information were retained.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The present findings are, however, consistent with those in the wider literature on context effects in recognition memory (e.g., Goh, 2005;Goldinger, 1996;Lim & Goh, 2012, 2013Peretz et al, 1998). In these studies, switching the speaker of the words and the timbre of the melodies from study to test, but keeping the identity the same, resulted in poorer recognition, as compared with the conditions in which both the central (word and melody identity) and peripheral (speaker and timbre) information were retained.…”
Section: Discussionsupporting
confidence: 48%
“…However, research using the recognition memory paradigm has shown that "peripheral" and contextual information are retained even when the task is to recognize the more "central" information. For example, people retain indexical properties of spoken words, such as voice attributes, when comparing performance between conditions where the same talker and word are presented during the study and test phases, versus a different talker but the same word during the test phase (e.g, Goh, 2005;Goldinger, 1996). Similar findings have also been found with melody recognition, where melodies with the same or a different timbre or format between study and test phases were manipulated (e.g., Lim & Goh, 2012, 2013Peretz, Gaudreau, & Bonnel, 1998).…”
mentioning
confidence: 99%
“…A strict version of this notion has been challenged by a burgeoning body of evidence over the past couple of decades demonstrating that linguistic processing is influenced by non-linguistic features of the speech signal, that is, by indexical information, including gender, talker identity, speaking rate, and the speaker's affective state (e.g., Goh, 2005;Goldinger, 1996;Johnsrude et al, 2013;Kaganovich et al, 2006;Mullennix & Pisoni, 1990;Palmeri et al, 1993;Schacter & Church, 1992;Sheffert & Fowler, 1995, and many others). This work has demonstrated that listeners are sensitive to changes in the indexical features of the input, such that listeners were found to be less accurate at identifying or recalling items when the surface characteristics changed from their initial exposure to the items relative to when the surface characteristics remained consistent.…”
Section: Integration Of Linguistic and Signal-intrinsic Non-linguistimentioning
confidence: 99%
“…Exemplar effects have been established in several priming experiments (e.g., Bradlow, Nygaard, and Pisoni, 1999;Craik and Kirsner, 1974;Goh, 2005;Goldinger, 1996;Janse, 2008;Mattys and Liss, 2008;McLennan et al, 2003;McLennan and Luce, 2005;Palmeri, Goldinger, and Pisoni, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Many articles in the literature point to a role of exemplars in word comprehension. This study investigates the robustness of these exemplar effects.Exemplar effects have been established in several priming experiments (e.g., Bradlow, Nygaard, and Pisoni, 1999;Craik and Kirsner, 1974;Goh, 2005;Goldinger, 1996;Janse, 2008;Mattys and Liss, 2008;McLennan et al, 2003;McLennan and Luce, 2005;Palmeri, Goldinger, and Pisoni, 1993).These experiments contained repeated words and the comprehension of the second occurrence of a word (the target) is expected to be facilitated by the first occurrence (the prime). Primes and targets were completely identical, that is the same token, or they differed in speech rate, time-compression, the realization of a certain segment (e.g., intervocalic /t,d/ produced as [t,d] or as a flap in American English), or the speaker's voice.…”
mentioning
confidence: 99%